Peter, Paul, and Mary: Names in the New Testament - Minnen, Peter van (Filología neotestamentaria, 2024)
In this two-part study, the names of individuals in the New Testament are first studied together, then one by one. In Part 1, the high incidence of Greek and Roman names is explained as the aftereffect of Hellenization and of enslavement and subsequent manumission by Romans in the first century BC. The names of John Mark are argued to derive from his paternal (John) and maternal (Mark) ancestors. Paul's name is shown to derive from his enslaved, then manumitted ancestors, who also provided him with Roman citizenship. Conclusions follow. In Part 2, the names are divided into Semitic, Greek, and Roman names. Thje discussion includes a critical review of recent scholarship on individual names. It also explains how to accentuate Semitic and Roman names in Greek. Apendix 1 lists all individuals in the New Testament with more than one name. Appendix 2 provides bibliography on names in t he New Testament world.